THE CONCEPT OF THE ARCHIPELAGIC PROVINCE AND ARCHIPELAGIC STATE IN THE PERSPECTIVE OF NATIONAL AND INTERNATIONAL LAW - Muhammad Risnain (Faculty of Law Universitas Lampung, 2021)
The concept of an archipelagic province in law number 23 of 2014 is interesting, especially international law of the sea and Indonesian national law. This research is due to the concept of an archipelagic State's special treatment, which is a concept derived from the 1982 United Nations Convention on the Law of the Sea (UNCLOS). This research accommodates the state's interests with special conditions for States that are geographical, social, political, and economic conditions by fulfilling the 1982 UNCLOS. The state is a subject of the international, but the archipelagic province receives special treatment from the central government in DAU and DAK. The problem in this research is how the concept of an archipelagic province and state is based on national and international law? The research method used is normative juridical research based on the applicable laws and regulations. The analysis is carried out using a descriptive method that explains the concept of an archipelagic province and state from the perspective of national and international law. The archipelagic state's international and national law concept cannot be applied to mutatis mutandis. The criteria for an archipelagic state as an intrinsic geographical, economic, defense and security, and political unit have historically been regarded as such. The 1982 UNCLOS and national laws cannot be applied in determining the criteria for an archipelagic province. According to the elucidation of Law Number 23 of 2014 concerning regional government, the archipelagic province based on geographical and cultural conditions is a moderate concept. This concept is beneficial in determining the characteristics of an archipelagic province.